UPAYA MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN BERBASIS STRUKTURED DYADIC METHODS (SDM) DI SMA NEGERI 1 PANYABUNGAN UTARA - Nurmaini Ginting; Samsiah Samsiah; Yusni Atifah (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2018)
This type of research this is a class action Research (PTK) and application of model-based learning, Structured Dyadic Methods (HR) on the material waste and recycling. Where the subject is students of class X. IPA SMA Negeri 1 Panyabungan North which consists of 25 students. While the techniques and data-collecting instruments namely observation and tests. Learning outcomes tests cycle students Biology I amounted to 76% and cycle II of 84.33%. Increased levels of student activity on the cycle I of 68.00% and cycle II 86.40% then increased the ability of teachers in managing learning cycle I of 75.00% and cycle II 91.00%. Keywords: class action Research, Structured Dyadic Methods, student activity.